The impact of bilingualism and code-switching on executive function performance - Özkara, Basak; Schneider, Raul; Cedden, Gülay; Stutterheim, Christiane von; Meyer, Patric (Frontiers in psychology, 2025)
Bilingualism, characterized by the use of two or more languages, places unique demands on executive functions (EFs), which are essential for managing cross-linguistic interference. This study investigates EF performance in Turkish-German bilinguals and German monolinguals across five domains: response inhibiton, working memory, task-switching, interference control, and attention. Additionally, the influence of habitual code-switching behavior on EF outcomes in bilinguals was explored using a novel scene description game designed to elicit naturalistic code-switching patterns, which approximate participants’ habitual bilingual language use. Results revealed that bilinguals outperformed monolinguals in task-switching accuracy, indicating enhanced cognitive flexibility. However, monolinguals exhibited superior working memory performance, as measured by d-prime scores on the N-Back task. No significant group differences were observed in attention-related tasks. Within the bilingual group, the Code-Switching Index (CS Index) emerged as a significant predictor of EF performance, particularly in tasks requiring interference resolution, such as the Stroop Interference test. Higher levels of code-switching were associated with increased susceptibility to Stroop interference, suggesting a complex trade-off between cognitive flexibility and interference control efficiency. These findings contribute to understanding the specific effects of bilingualism on EF performance, highlighting domain-specific adaptations that emerge in some EF components but are absent in others. By integrating insights from EF research with contemporary theories of cognitive control and bilingual language use, this study underscores the importance of analyzing individual EF domains and accounting for diverse bilingual experiences, such as code-switching behavior, to better understand the cognitive mechanisms underlying bilingualism.
Veröffentlicht: 03. Dezember 2025
Gesehen am 09.02.2026